A HEIDEGGERIAN ANALYSIS OF FUNDAMENTALISM: A BRIEF DISCUSSION - Colin O’Connell (Journal of Dharma, 1990)
In the past ten years there have been. It seems clear signs of a turn to the right in matters political and religious. In some quarters this has been characterized as neo-conservatism - a generic term used to cover a host of attitudes and behaviours. Accompanying this shift but not identi- cal to it. is a corresponding rise in fundamentalism. One need only point to the Islamic revolution in Iran or to the Moral Majority in the United States, both of which have tried to push the political agenda in afar more conservative direction. A whole spectrum of explanations and hypotheses - some more satisfying than others - have been advanced to account for this shift.